HEGEMONI BUDAYA INDUSTRI DALAM PENDIDlKAN KONTEMPORER - adminBambang Syaeful Hadi; Iffah Nurhayati (Jurnal Cakrawala Pendidikan, 2002)
The industrial culture as a product ofan increasingly industrial society has greatly influenced the educational system.Its hegemony in the educational system has shifted educationalidealism. Since the industrial culture assumes that man is afactor in production, the aim of education has started tochangefrom its original course for the sake of meeting thedemandsof the industrial field, the market for its product. Afurther consequence of this is that the output of educationno longer meets the expectation concerning what is essentiallyworthy to be the objectiveof education, which is to develophuman resources with all their potentials into better individualswho are independent and increasingly awareof the essence oftheir humanity.There are supposed to be three main agents of education,i.e., the family, the school, and society. However, today the schooltends to be the main support ofeducation while the educatiomil .system runningat schools now in operation has diverged fromthe original idealismofeducation. Education in one alternative.religion, Islam, has not achieved what is intended by the Koranand Hadits, either, because there are not yet any adequate willand ability among Moslems to interpret creatively the religiousteachings and transfer them into some formof educational system together with its operational steps.The hegemonyofindustrial culture has "forced" the executorsof education to use educational concepts and designs thatsupport industrial needsin order that the educational output wouldbe wel1-preparedto enter the job market. The educational systemis then also designed in such a way that practical and pragmaticteaching materials have a greater portion than the students'values in ethics, social matters, religiosity, behavior, and mentality. This phenomenon will speed up a processofdehumanization thatwil1 eventual1y result in social and national destruction.Therefore, there needto be steps of reorientation, restructuring,and innovation in the educational system that are based onpotentialsofthe self and stick to religious values to achieve thereal educational objective